2020
DOI: 10.1051/0004-6361/202037744
|View full text |Cite
|
Sign up to set email alerts
|

Effect of binary evolution on the inferred initial and final core masses of hydrogen-rich, Type II supernova progenitors

Abstract: The majority of massive stars, which are the progenitors of core-collapse supernovae (SNe), are found in close binary systems. In a previous work, we modeled the fraction of hydrogen-rich, Type II SN progenitors whose evolution is affected by mass exchange with their companion, finding this to be between ≈1/3 and 1/2 for most assumptions. Here we study in more depth the impact of this binary history of Type II SN progenitors on their final pre-SN core mass distribution, using population synthesis simulations. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 140 publications
0
34
0
1
Order By: Relevance
“…This indicates that the late-stage evolution of massive stars is more complicated than what is previously thought. Even for RSGs whose evolution is not significantly affected by binary interactions (though see Zapartas et al 2019Zapartas et al , 2021, mass loss due to the late-stage nuclear fusion can still produce a CSM with diverse properties that interacts with the SN shock at early times (Quataert & Shiode 2012;Fuller 2017;Wu & Fuller 2021). While studies of CSM properties with moderately-sized samples of SNe II-P are present (e.g., Morozova et al 2018), the Vera Rubin Observatory will be able to produce multi-band light curves of all SNe II-P out to about 400 Mpc, allowing for a truly systematic study of CSM interactions around SNe II-P. With the pre-detection of SNe II-P progenitors reliant on serendipitous pre-explosion HST imaging, if a connection between the CSM properties and progenitor properties can be made, this would greatly enhance our capability to study the late-stage evolution of RSGs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicates that the late-stage evolution of massive stars is more complicated than what is previously thought. Even for RSGs whose evolution is not significantly affected by binary interactions (though see Zapartas et al 2019Zapartas et al , 2021, mass loss due to the late-stage nuclear fusion can still produce a CSM with diverse properties that interacts with the SN shock at early times (Quataert & Shiode 2012;Fuller 2017;Wu & Fuller 2021). While studies of CSM properties with moderately-sized samples of SNe II-P are present (e.g., Morozova et al 2018), the Vera Rubin Observatory will be able to produce multi-band light curves of all SNe II-P out to about 400 Mpc, allowing for a truly systematic study of CSM interactions around SNe II-P. With the pre-detection of SNe II-P progenitors reliant on serendipitous pre-explosion HST imaging, if a connection between the CSM properties and progenitor properties can be made, this would greatly enhance our capability to study the late-stage evolution of RSGs.…”
Section: Discussionmentioning
confidence: 99%
“…Physical processes responsible for mass loss may include stellar winds, minor eruptive mass loss associated with late-stage nuclear burning instabilities, binary interactions, and likely combinations thereof (Smith 2014, and references therein). However, the rates and quantitative contributions from each of these processes in different types of progenitor stars remain the subject of ongoing research (see, e.g., pre-SN instability and outburst, Wu & Fuller 2021;Leung & Fuller 2020; binary effects on stellar structure, Laplace et al 2020;Zapartas et al 2021; and new stellar wind prescriptions Björklund et al 2021;Kee et al 2021). Observations of the resulting core-collapse supernova (CCSN) interacting with the CSM can probe its density structure, providing clues about its origin and the properties of the progenitor star.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the vast majority of stars massive enough to reach core-collapse are evidence for surviving companions after CCSNe (e.g., Maund et al 2004;Fox et al 2014;Ryder et al 2018). Binary population synthesis studies have recently shown binary interaction should also affect ∼ 50% of hydrogenrich (type II) SNe (e.g., Eldridge et al 2018;Zapartas et al 2019;Zapartas et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Bruzual & Charlot 2003;Maraston 2005; Le Borgne et al 2004), there is an increasing recognition that its effects are important, particularly when interpreting young and distant stellar populations, or in determining the rates of transient objects (e.g. Vrancken et al 1991;Tutukov et al 1992;Vanbeveren et al 1998;Zhang et al 2013;Stanway et al 2014;Eldridge et al 2019;Wilkins et al 2016;Ma et al 2016;Steidel et al 2016Steidel et al , 2018Chrimes et al 2020;Götberg et al 2020;Zapartas et al 2020). The fraction of massive stars affected by a binary companion during their evolution is clearly substantial, and cannot be entirely neglected (Sana et al 2012(Sana et al , 2013.…”
Section: Introductionmentioning
confidence: 99%